Mantra Di Desa Wolotolo Kecamatan Detusoko Kabupaten Ende - Yakobus Pati (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
Research on mantras in Wolotolo Village, Detusoko District, Ende Regency aims to describe the form and function of mantras for the people who inhabit the area. The research method used is descriptive qualitative method with data collection techniques used are observation and interview techniques. The results showed that the mantra tuku ae uja (resistant to rain), mantra joka tu (reject bala), and mantra rago nitu (exorcise spirits) are in the form of prayer, because the three mantras have a special purpose or intention that is conveyed by requesting. These mantras have a religious function, namely as a society's appreciation of God Almighty as the Creator of man and the universe, an educational or educational function that teaches people to be grateful for God's creation, and the function of love as an attitude of life to respect the universe as a a place to live, humans, and all living things on earth.